Prospecção de água subterranea por eletrorresistividade em terrenos cristalinos - Garces, Alexsandro dos Santos (2019)
his dissertation deals with groundwater prospecting in crystalline terrains using the Electroresistivity Method - 1D Gradient Arrangement, developed in the municipality of Iracema / CE. The municipality is located in pre-Cambrian crystalline terrain of Provincia Borborema and in the so-called “drought polygon”, characterized by semi-arid climate, high annual evapotranspiration rates, with poorly distributed rainfall, all these factors have contributed to water scarcity in the region. region, and with this, the population has been suffering throughout its history. As a result of the lack of water in the population of this municipality, an emergency groundwater catchment program was developed by the Superintendencia de Hydraulicas (SOHIDRA) to serve the municipal headquarters and the towns of Chapada, Jurema, Mororo, Foz de Cima, Foz / German, High Board, Serra Vermelha, Agua Nova / Ema, Bom Sucesso / Ema, Bom Sucesso Farm and Bom Sucesso Farm. This research involved geological mapping, remote sensing, tubular well registration and geophysical survey, which resulted in the location and construction of 30 tubular wells. From the results, a Geoelectric Anomaly Detection (DAGE) method was developed, based on the geoelectric anomaly analysis and resistivity values ​​obtained in the field curves, lithologies and tubular wells. Two types of curves were classified, the first presents a curve with “U” geoelectric anomaly, showing two or more values ​​of low resistivity and occur mainly in gneissic rocks of Jaguaretama Complex, all 20 wells located in this type of curves and lithology were productive. and half of them had satisfactory flow rates, with a maximum flow rate of 16m³ / h. The second shows a curve with “V” geoelectric anomaly, has only a low resistivity value and occurs in the granitic rocks of Pluton Pereiro and Pluton Without Denomination, the 10 wells located in these curves and lithology showed low productivity with flows less than 1, 10 m³ / h and 4 of them were dried. Based on the obtained results, it can be concluded that the correct application of the Electroresistance Method, following the previously defined criteria, such as the execution of the profiles in areas where fractured gneissic rocks occur and following a direction. Parallel to its foliation (NE-SW) thus crossing open fractures of WE direction, integrated to the Geoelectric Anomaly Detection Method presented a high index of hit (80%) in the well locations, with average flow 3,56m³ / h, and that the gneissic rocks of the Jaguaretama Complex that occur in the municipality of Iracema have a good hydraulic potential.